An Automated Tool for MC/DC Test Data Generation - Ariful, Haque; Irman, Khalil; Kamal Z., Zamli (2014)
Structural testing is often the most common sought criteria for exercising aspects of control flow (i.e. such as statement, branch and path coverage). In many cases, criteria based on statement, decision and path coverage appears sufficiently effective for testing (in terms of selecting the appropriate test cases for testing consideration) the various parts of the software implementation. In other cases involving complex predicates, criteria based on statement, branch, and path coverage appear problematic owing to the problem of masking (where one variable is “masking” the effects of other variables). Addressing this issue, this paper discusses the design and implementation of an automatic test data generation called MC/DC GEN for structural testing based on Multiple Condition/Decision Coverage (MC/DC). In doing so, this paper also highlights the possible adoption of MC/DC GEN for practical use.